The Impact of Credit Risk, Liquidity Risk, and Operational Risk on Profitability of Government-Owned BPRs in West Java and Banten During the 2019–2023 Period - Diana Rofaidah; Cecep Taufiqurrochman; Lilis Saidah Napisah (Eduvest - Journal of Universal Studies, 2026)
This study aims to analyze the effect of credit risk (Non Performing Loan / NPL), liquidity risk (Loan to Deposit Ratio / LDR), and operational risk (Operating Costs to Operating Income/BOPO) on profitability (Return on Assets / ROA) at People's Credit Banks (BPR) owned by the Regional Governments of West Java and Banten Provinces for the 2019–2023 period. The research method used is quantitative with a descriptive and verifiable approach, using secondary data in the form of BPR's annual financial statements. The data analysis technique used is panel data regression. The results of the study show that simultaneously credit risk, liquidity risk, and operational risk have a significant effect on the profitability of BPR. Partially, credit risk (NPL) and liquidity risk (LDR) have no significant effect on ROA, while operational risk (BOPO) has a negative and significant effect on ROA. These findings indicate that operational efficiency is the dominant factor in increasing the profitability of BPRs owned by local governments. Therefore, BPRs need to strengthen operational cost control, improve the quality of risk management, and maintain liquidity balance to achieve healthy and sustainable financial performance.